How does the energy consumption structure affect the green economic development? A spatial impact analysis - Zhang, Shumin; Wang, Jing; Guan, Jiawei (Frontiers in Environmental Science, 2024)
Background Optimizing the energy consumption structure (ECS) is conducive to promoting the efficiency and quality of regional green economic development (GED). This paper discusses the current situation of green economic development (GED) in China and how optimizing the energy consumption structure (ECS) can promote green economic development (GED). Methods A systematic literature search (from January 2013 to July 2024) was conducted using the keywords “green economic development” and “energy consumption structure” in the following databases: Web of Science, Embase, Science Direct, and PubMed. In this paper, the entropy method was used to measure the GED indicator system, Arcgis drawing was applied to show the current status of GED development, and the theme of this paper was investigated by constructing the basic regression model, Spatial Durbin model, mediating effect model, and moderating effect model. Two researchers independently screened and extracted data. Results The analysis of empirical tests in 30 provinces yielded the following results: The overall development of China’s GED shows a fluctuating upward trend. However, there is a regional development imbalance, and the development level of the eastern region is significantly higher than that of the central and western regions. The optimization of ECS contributes significantly to the improvement of GED. And the effect of optimizing ECS on GED has an apparent spatial spillover effect. The optimization of ECS in neighboring regions also promotes the increase of GED in the region, and this feature is more obvious in the central and western regions. The spatial effect of ECS optimization on GED is shown as Central Region > Western Region > Eastern Region. The total effect of the upgrading of the energy consumption structure and its impact on surrounding areas is shown in the following regions: Western region > Central region > Eastern region. The analysis of the mechanism effect shows that upgrading industrial structure is the main mechanism for optimizing ECS on GED. Discussion The results show that the optimization and upgrading of ECS is the driving force behind the development of GED, and that there is a need to break down barriers between regions to promote the common development of GED, as well as to play a role in the mechanism of industrial structure.